Strategi Promosi Periklanan Di Media Sosial Dalam Meningkatkan Pendapatan Client PT. Borneo Digital Marketing Ditinjau Dari Perspektif Ekonomi Islam - Nur Fitriyah; Darmawati Darmawati; Tika Parlina (Borneo Islamic Finance and Economics Journal, 2022)
Abstract The background discusses in the current digital era, many business people are competing to market their products or services online through social media networks by advertising. Therefore, promotion strategies through social media are indispensable, both for large and small businesses. The purpose of this study was to determine the advertising promotion strategy on social media carried out by PT. Borneo Digital Marketing in increasing client income of PT. Borneo Digital Marketing and knowing the picture of the sharia economy about advertising promotion strategies on social media in increasing the income of PT. Kalimantan Digital Marketing. This study uses field research to explore data sourced from the research location and is descriptive qualitative, namely research that aims to obtain a complete picture of something being researched. Sources of data are 38 sources from interviews conducted with the CEO, 7 employees and 30 clients of PT. Kalimantan Digital Marketing. Data collection techniques are interviews, observation and documentation. The data analysis technique uses the method according to Miles And Huberman, namely data collection, data reduction, data presentation and data verification. The results of the research are advertising promotion strategies on social media used by PT. Borneo Digital Marketing, namely four specific advertising promotion strategies such as paid media vs organic media strategies, performance strategies, intent strategies, and marketing channel strategies. Judging from the tables and graphs of client income, the four special promotion strategies have been able to increase client income of PT. Borneo Digital Marketing. Islamic economics review of advertising promotion strategies on social media used by PT. Borneo Digital Marketing applies Islamic economic principles such as Tawhid, Morals: Shidiq (true and honest), Tablig (speaking truth), Amanah (trustworthy) and Fathanah (intelligent), Balance, individual freedom and justice. Keywords: Promotion Strategy, Advertising, Social Media, Income, Islamic Economic Perspective